Perbedaan Karakterisasi Ftir Antara Getah Perca Indonesia Dengan Getah Perca Kedokteran Gigi - Annisa Hasna Nurzahra Tauziri; Kosterman Usri; Opik Taopik Hidayat (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
Getah perca or known as gutta percha is the most widely used for the root canal filling material. Indonesia has a big potency to product dental gutta percha, as it is the biggest country that has productions of natural gutta percha. Indonesia is conducting natural gutta percha at PT. Perkebunann Nusantara VIII Cipetir-Jawa Barat. Chemical composition and bond are very important to be found out before making the root canal filling material from natural gutta percha. This study purposed to know the chemical composition differences between natural gutta percha and dental gutta percha using Fourier Transform Infrared Spectrometry (FTIR) characterizations. The methode is descriptive study that studies the FTIR Characterization between natural gutta percha and dental gutta percha. The characterized samples, each consist 20 mg of natural gutta percha and 20 mg dental gutta percha.The IR results the difference of transmission between natural gutta percha and dental gutta percha. Both show the presence of hydroxyl groups in the material indicates that the process is oxidative, but the dental gutta percha contain pro oxidant that increase the oxidation. The conclusion of this study showed there is FTIR characterization difference between natural gutta percha and dental gutta percha.